Analisis Yuridis Terhadap Kebebasan Pers Di Indonesia Dan Malaysia - Lu Sudirman; Miming Utami (Fakultas Hukum, Universitas Internasional Batam, 2015)
Human rights are basic rights that naturally inherent in human beings and therefore should not be taken away by anyone. The establishment of freedom of the press is a part of Human Rights. Freedom of press has been arranged in a state of laws and laws of Indonesia and Malaysia.Methodology used in this research is the normative legal research-based on comparative law. The data used in this study is a secondary data obtained from literature (library research). Once all the data is collected, then processed and analyzed to find the legal issues that are the object of study and conclude, then described descriptively. These results indicate that the legal provisions on freedom of dispersions in Indonesia and Malaysia has similarities and differences. The provision of equality provisions press freedom in Indonesia and Malaysia are constitutional arrangements in each country, the scope of freedom of the press, and criminal sanctions. While the provision is the difference in press freedom conditions recognition liberated press, the press council, and the code of conduct.